A study of the early development of the root systems of various grass species, and, a study of the importance of various roots, particularly the seminal roots to Lolium perenne : thesis submitted in part fulfilment for the degree of Master of Agricultural Science in Plant Husbandry, University of New Zealand - Yates, Milton Earle (Massey University, 1950)
New Zealand is essentially a land of pasture. Greater reliance is placed on pastures for the sustenance of stock by the farmer in New Zealand than probably anywhere else in the World. The study of pastures is theretore of paramount importance to the national welfare of New Zealand and their improvement will be reflected in raised living standards and at the same will provide more food for the hungry world of today. There is no doubt that New Zealand is favoured by an equable climate and well distrtbuted rainfall which enables her to derive a considerable portion of her wealth trom grasslands. Nevertheless we have had to adopt farming methods to suit the environment so that the greatest benefits may be derived from the natural advantages with which New Zealand is endowed. New Zealand has proceeded a long way since the early days of her farming when little was known of the environmental requirements of individual species in order that they may produce to their maximum. It is unquestionable that much of the progress already made in grassland husbandry in this country is due to the wide range of trials conducted by the Department of Agriculture and Grasslands Division, D.S.and I.R., particularly over the last quarter of a century. Much has been learnt in the past and investigations being pursued at the present time will no doubt be reflected by improved methods of grassland husbandry with consequent increased pasture production in the future. [From Introduction]
Best copy available due to the condition of the orginal.
Keywords: Roots (Botany); Grasses; Lolium perenne